Glutamate load fosters spreading depolarization under osmotic stress in brain slices - Frank, Rita; Marinesco, Stephane; Bari, Ferenc; Menyhárt, Ákos; Farkas, Eszter (Frontiers in Cellular Neuroscience, 2026)
IntroductionCerebral edema is a hallmark of lesion progression after acute ischemic stroke (AIS) and a major contributor to the evolution of spreading depolarizations (SDs). SDs trigger extracellular glutamate accumulation and excitotoxic injury, yet the mechanisms linking edema formation, glutamate dysregulation, and SD dynamics remain incompletely understood. Here, we investigated how inhibiting glial swelling and volume-regulated glutamate release, or blocking neuronal ionotropic glutamate receptors alters SD features under hypo-osmotic stress in vitro.MethodsAcute 350-µm-thick brain slices were prepared from male Wistar rats (n = 24). Edema was induced using hypoosmotic medium (130→60 mM NaCl), and SD was triggered by hypoxia. SD evolution and extracellular glutamate levels were monitored using local field potential recordings, intrinsic optical signal imaging, and enzyme-based glutamate biosensors. Astrocyte swelling was reduced by blocking AQP4+NKCC1 (TGN-020 + bumetanide) and VRAC channels (DCPIB), while neuronal NMDA and AMPA/kainate receptors were antagonized with MK-801 + CNQX.ResultsInhibition of AQP4, NKCC1, or VRAC channels restricted the cortical area invaded by SD, shortened SD duration, and reduced extracellular glutamate accumulation. In contrast, blockade of NMDA or AMPA/kainate receptors markedly decreased SD propagation and glutamate buildup. Both astrocytic and neuronal interventions disrupted typical SD initiation patterns, producing atypical, multifocal SD events.DiscussionThese findings demonstrate that astrocyte volume regulation and neuronal ionotropic glutamate receptors jointly shape SD characteristics under osmotic stress, identifying astrocytic water/ion homeostasis and glutamatergic signaling as potential therapeutic targets to limit excitotoxic injury in acute cerebrovascular disease.